The roles of growing up milk on growth and anemia prevention in children under 5 years of age - Sunardi, Diana; Budiati Sutanto, Luciana; Chandra, Dian Novita; Shabrina, Arifah; Ratih, Mia Puspita (Indonesian Nutrition Association, 2024)
Background: Adequate nutrition during the early years of life is necessary for good growth, development, and long-term health outcomes. The first 1000 days of life are a critical time for nutrition. Aims: This literature review aimed to evaluate the role of growing up milk on growth, stunting, and anemia prevention of under-five children. Methodology: This study used a literature review approach, searching three databases: PubMed, Google Scholar, and Cochrane. The inclusion criteria in this literature review were 1) randomized clinical trials, systematic review, and meta-analysis, 2) studies conducted over the last 10 years, 3) available in full text, 4) written in Indonesian or English, and 5) Research studies conducted in humans. Result: We identified 3 publications, that matched the inclusion criteria and research aims, including 2 original articles from Lovell AL, et al and Cervo MCM, et al, and 1 meta-analysis by Brooker PG et al. Fortified milk (GUM) consumption significantly had a positive impact on nutritional status, especially growth and hemoglobin status (anemia). Conclusion: Fortified milk (GUM) consumption is a solution to macro-micronutrient adequacy in under five children. More efforts are needed to conduct studies in Indonesia on GUM and address specific nutrients that may promote linear growth, reverse stunting and anemia in children.